Penurunan Jumlah Cacat Produksi Melalui Pendekatan Seven Tools Of Quality - Gerry Gerry; Dyah Budiastuti (Bina Nusantara University, 2014)
PT Cipta Lestari Packindo is a manufacturing company engaging in the manufacture of cardboards. In its operational activities, the company experiences problems like defects or faults in the cardboard production process. Therefore, there’s a need for continuous improvements so that the company won’t suffer either from loss or cost of quality that will appear in the future. To achieve that, the seven tools of quality approach were used in an attempt to repair and reduce the level of errors and the defects in production. Results of this research found there are eight types of the cardboard defection occurred during the productions. By using pareto diagram, research found three major problems that took the biggest roles: pieces that are not aligned with the rotary engine, pieces that are not aligned with the coak engine, and missing in the printing process. In the analysis process of the reduction of defective productions within the three major problems, there are six factors causing the defections: men, machines, methods, measurements, materials, and environments—with men and machines as the biggest contributors. By doing continuous improvements, the level of the defective production will decrease eventually.